Ẓāhira Ḥaraka al-Ṣhibān al-Nahḍīyya al-Fikrīyya Dirāsah an Majmu’I al-Dirāsāt al-‘Islāmīyya al-‘Itimā’īyya (LKiS) bi Yogyakarta - M Mahasin (Al-Jami'ah Research Centre, 1997)
In 1989 a group of students in Yogyakarta, who were brought up in the traditional Islam, managed to arrange several meetings to discuss some issues of Islam and especially Nahdlatul UIama. The success of the meetings pushed them to establish an institute wherein they could realize their dreams of the amelioration of the condition in which they and the other children of Nahdlatul Ulama live. Thus they stablish LKiS (Lembaga Kajian Islam dan Sosial or Institute for Islamic and Social Studies). Their activities fall into three categories: (l) research, (2) publication and (3) study, education and training. It is interesting to note that they have published books contain of ideas far from being traditional, but some of them offer radical transformation of Islamic understanding and praxis. In this article the writer tries to answer questions on the underlying reasons for their somewhat controversial al activities, their endurance and their traditionality. [Beberapa anak muda di Yogyakarta yang dibesarkan di kalangan Islam